2018
DOI: 10.1002/adfm.201803990
|View full text |Cite
|
Sign up to set email alerts
|

Optothermoplasmonic Nanolithography for On‐Demand Patterning of 2D Materials

Abstract: Since the first discovery of graphene, 2D materials are drawing tremendous attention due to their atomic thickness and superior properties. Fabrication of high-quality micro-/nanopatterns of 2D materials is essential for their applications in both nanoelectronics and nanophotonics. In this work, an all-optical lithographic technique, optothermoplasmonic nanolithography (OTNL), is developed to achieve high-throughput, versatile, and maskless patterning of different atomic layers. Low-power (≈5 mW µm −2 ) and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 63 publications
0
47
0
Order By: Relevance
“…The O, C, and Au atoms are represented by red, brown, and gold colored balls in the right panel, respectively. Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Laser Treatment Of Graphene and Its Derivativesmentioning
confidence: 99%
“…The O, C, and Au atoms are represented by red, brown, and gold colored balls in the right panel, respectively. Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Laser Treatment Of Graphene and Its Derivativesmentioning
confidence: 99%
“…To decouple the optical heating and scattering, we applied a thermoplasmonic substrate as the heat source (see Supplementary Fig. 4 for the structure and Methods for fabrication procedure) 32 . In addition, we selected polystyrene (PS) and titanium dioxide (TiO 2 ) nanoparticles for the control experiments because of their negligible optical absorption and distinct scattering properties (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been recently observed that the lithographic techniques using electrons or ions may induce structural damage in 2D materials, [ 9 ] or add resist contaminations that need to be removed by plasma cleaning. [ 10 ] Laser ablation is a resist‐free, one‐step alternative, [ 11–13 ] but the optical diffraction limit prevents its use where sub‐micrometer resolution is required. Bottom‐up techniques, like chemical vapor deposition and site‐selective growth, [ 14,15 ] allow for scalability and high resolution.…”
Section: Figurementioning
confidence: 99%